Cutaneous immunopathology of long‐standing complex regional pain syndrome. (25th February 2015) - Osborne, S.; Farrell, J.; Dearman, R.J.; MacIver, K.; Naisbitt, D.J.; Moots, R.J.; Edwards, S.W.; Goebel, A.
Abstract Background Both increased mast cells numbers and raised immune mediator concentrations indicate immune activation in the affected skin of patients with early complex regional pain syndrome (CRPS), but little is known about regional immune cell involvement in late‐stage CRPS. The aim of the current study was to determine skin immune cell populations in long‐standing CRPS. Methods Using 6‐mm skin punch biopsies from CRPS‐affected and non‐affected tissues, and a combination of chemical and immunofluorescence staining, we examined the density and function of key cell populations including mast cells, epidermal Langerhans cells (LCs) and tissue resident T‐cells. Results We found no significant differences in either overall immune cell infiltrates, or mast cell density between CRPS‐affected and non‐affected sub‐epidermal tissue sections, contrasting recent findings in early CRPS by other groups. However, CD1a+ LC densities in the epidermal layer were significantly decreased in affected compared to non‐affected CRPS limbs (p < 0.01). T‐cell clones isolated from CRPS‐affected sub‐epidermal tissues displayed a trend towards increased IL‐13 production in ELISPOT assays when compared to T‐cells isolated from non‐affected areas, suggesting a Th2 bias. Conclusions Immune cell abnormalities are maintained in late‐stage CRPS disease as manifest by changes in epidermal LC density and tissue resident T‐cell phenotype.